2005
DOI: 10.1007/s00535-004-1494-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients with advanced hepatocellular carcinoma receiving hepatic arterial infusion chemotherapy

Abstract: Patients who had advanced HCC with favorable hepatic reserve capacity and a lower AFP level were suitable candidates for HAIC. Moreover, the regimen using low-dose CDDP and 5-FU with leucovorin/isovorin may be suitable for advanced HCC patients, because of the improvement in the response rate and survival compared with the low-dose CDDP and 5-FU regimen without leucovorin/isovorin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 38 publications
6
94
1
Order By: Relevance
“…It was reported that administration of lower doses of 5-FU for longer times was more effective in producing direct cytotoxic effects in human tumor cells than when administered at higher doses for shorter times [21]. Many investigators have reported the efficacy of this combination therapy for advanced HCC [22,23,24,25]. Okuda et al [26] reported that the CR rate and effective response rate of HAIC using cisplatin and 5-FU were 29.0 and 71.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that administration of lower doses of 5-FU for longer times was more effective in producing direct cytotoxic effects in human tumor cells than when administered at higher doses for shorter times [21]. Many investigators have reported the efficacy of this combination therapy for advanced HCC [22,23,24,25]. Okuda et al [26] reported that the CR rate and effective response rate of HAIC using cisplatin and 5-FU were 29.0 and 71.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the US, where there is no national screening program, the majority of HCC patients present at an advanced phase of their disease, either due to the severity of the underlying cirrhosis or the extent of their HCC. There has not so far, to our knowledge, been a large prospective study of these advanced unresectable HCC patients; although, several small series having evaluated prognostic factors in these patients [8,20,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 However, an overall response rate to HAIC of 22 to 71% has been reported, 17 and HAIC is not effective for all patients. The median survival times reported in responders to HAIC was 18.4 to 31.6 months and in nonresponders, 5.4 to 6.7 months, 15,18 and the survival rate was significantly higher of responders than nonresponders. Thus, the prediction of patients' responses to HAIC would be very useful.…”
Section: Introductionmentioning
confidence: 87%